Β‐catenin and Kras/Foxm1 signaling pathway are critical to restrict Sox9 in basal cells during pulmonary branching morphogenesis. Issue 5 (8th March 2016) - Ustiyan, Vladimir; Zhang, Yufang; Perl, Anne‐Karina T.; Whitsett, Jeffrey A.; Kalin, Tanya V.; Kalinichenko, Vladimir V.
Abstract : Background : Lung morphogenesis is regulated by interactions between the canonical Wnt/β‐catenin and Kras/ERK/Foxm1 signaling pathways that establish proximal‐peripheral patterning of lung tubules. How these interactions influence the development of respiratory epithelial progenitors to acquire airway as compared to alveolar epithelial cell fate is unknown. During branching morphogenesis, SOX9 transcription factor is normally restricted from conducting airway epithelial cells and is highly expressed in peripheral, acinar progenitor cells that serve as precursors of alveolar type 2 (AT2) and AT1 cells as the lung matures.Results : To identify signaling pathways that determine proximal‐peripheral cell fate decisions, we used the SFTPC gene promoter to delete or overexpress key members of Wnt/β‐catenin and Kras/ERK/Foxm1 pathways in fetal respiratory epithelial progenitor cells. Activation of β‐catenin enhanced SOX9 expression in peripheral epithelial progenitors, whereas deletion of β‐catenin inhibited SOX9. Surprisingly, deletion of β‐catenin caused accumulation of atypical SOX9‐positive basal cells in conducting airways. Inhibition of Wnt/β‐catenin signaling by Kras G12D or its downstream target Foxm1 stimulated SOX9 expression in basal cells. Genetic inactivation of Foxm1 from Kras G12D ‐expressing epithelial cells prevented the accumulation of SOX9‐positive basal cells in developing airways.Conclusions : Interactions between the Wnt/β‐catenin and the Kras/ERK/Foxm1 pathways are essential to restrict SOX9 expression in basal cells. Developmental Dynamics 245:590–604, 2016 . © 2016 Wiley Periodicals, Inc. Key findings: β‐Catenin Stimulate Sox9 in Peripheral Lung Epithelial Progenitors. β‐Catenin Restrict Sox9 in Basal Cells. Kras stimulates Sox9 in Basal Cells via Foxm1.